(untitled) (Филолошки студии, 2019)
In the image of Great Patriotic War in the novel “The General and his Army” (“General i ego armija”) by G. Vladimov there is an allusion to “War and Peace” by L. Tolstoy. Tolstoy’s influence on Vladimov lead to the negative attitude of the author to the totalitarian policy of the soviet government. The same effect has an allusion to “Hadgy-Murat” by L. Tolstoy in the story “Causcasian” by V. Makanin. In the stories “The Crescent has come out of Mist” and the “To See a Tree” by V. Vishneveckoy there are some references to F. Dostoevskiy (the author of “Crime and Punishment”) and to philosophy of so called “live life” of such characters as Mishkin and Karamzin. In L. Petrushevskaya’s and T. Tolstaya’s prose the issue of “a little person” typical of Russian classical literature is considered as an existential problem of constantly dramatical position of a person in a hostile environment. As for the issue of resignation and sacrifice modern writers L. Ulickaya and T. Tolstaya in their works demonstrate a tense opposition to Dostoevskiy’s philosophy, they prefer characters of moral class of Natasha Rostova (L. Tolstoy “War and Peace”) to “eternal Sonechka Marmeladova” (F. Dostoevskiy “Crime and Punishment”).